Disinfection of dental impressions: knowledge and practice among dental technicians - Al Mortadi, Noor (Clin Cosmet Investig Dent, 2019)
Background: Dental impressions are a common source for transmission of infection between dental clinics and dental labs. Dental impressions can be cross-contaminated by patient’s saliva and blood, which then cross-infect the dental casts poured from the impressions. Objective: To evaluate the current practices of disinfection of dental impressions and their protocols and to assess the knowledge of cross-infection control among dental technicians in Jordan. Method: Dental technicians (n=85) completed a self-administered questionnaire about their practices of disinfection for dental impressions. Results: The distribution of dental technicians was 63.8% fixed prosthodontics, 23.5% removable prosthodontics, 7.8% orthodontics, and 4.8% maxillofacial prosthodontics. The majority of the laboratories did not have instructions related to disinfection of impressions. About 50% of technicians were vaccinated against HBV. About 44.7%, and 42.9% of labs reported that they never disinfect alginate or silicon impressions, respectively. In addition, the majority of lab owners (53%) believed that the dentist should disinfect the impressions before shipping them to dental laboratories, while (45%) believed that disinfecting the impressions is the responsibility of the dental assistant. Moreover, about 38% of this study population reported not using gloves in their labs. In those labs were disinfection was used, 51% used spray disinfection whereas 32.6% used immersion disinfection. The cost of disinfectant was ranked as the most important factor (51.3% of the cases) for the dental technician to choose the disinfectant followed by its effectiveness. Conclusion: Dental technician practices in impression disinfection was not satisfactory, therefore, education programs about impression disinfection are needed.